(untitled) (Research, Society and Development, 2022)
Objective: This study aimed to identify and examine studies on CPR-IC and its main conducts. Method: It was a scoping review study conducted according to the recommendations of The Joanna Briggs Institute, in the MEDLINE, CINAHL, Scopus and Web of Science databases. Results: Fourteen studies were included in the review. All selected studies were published in English, between 2009 and 2017, mostly from Europe and North America. Evidence described CPR-IC as an under-recognized event by health professionals, however, when it occurs, the main conducts performed by the multidisciplinary team include interruptions of cardiopulmonary resuscitation to check the pulse and physical restraint to continue resuscitation maneuvers and sedation. Nevertheless, it was observed that there is no consensus among specialists in managing this phenomenon. Conclusion: The studies indicate the need to standardize care management guidelines and conduct guidance.